2012
DOI: 10.3390/ani2030472
|View full text |Cite
|
Sign up to set email alerts
|

Double Muscling in Cattle: Genes, Husbandry, Carcasses and Meat

Abstract: Simple SummarySelection for an increased meatiness in beef cattle has resulted in double-muscled (DM) animals, owing to the inactivation of the myostatin gene. These animals are characterized by an excellent conformation and an extremely high carcass yield, coinciding with a reduced organ mass. As a consequence, voluntary feed intake is reduced, but feed efficiency is considerably improved, although maintenance requirements are not clearly reduced. DM animals are more susceptible to respiratory disease, stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 197 publications
8
73
0
15
Order By: Relevance
“…Cabrera Estrada et al (2004) showed that voluntary DM intake of dairy cows increases as the internal water content of roughages decreases. This phenomenon may even be more important in double-muscled animals because of their reduced feed intake capacity (Fiems, 2012). Furthermore, we found that dietary DM content is one of the most important feed characteristics influencing intake of growing double-muscled bulls (Fiems et al, 2002a).…”
Section: Supplementation Of Grazing Double-muscled Heifersmentioning
confidence: 73%
See 2 more Smart Citations
“…Cabrera Estrada et al (2004) showed that voluntary DM intake of dairy cows increases as the internal water content of roughages decreases. This phenomenon may even be more important in double-muscled animals because of their reduced feed intake capacity (Fiems, 2012). Furthermore, we found that dietary DM content is one of the most important feed characteristics influencing intake of growing double-muscled bulls (Fiems et al, 2002a).…”
Section: Supplementation Of Grazing Double-muscled Heifersmentioning
confidence: 73%
“…We previously reported a BW loss during the last months of gestation in BBDM heifers (Fiems and De Brabander, 2009), which can be a consequence of an insufficient feed intake because of the competition for abdominal space. This phenomenon may be more important in double-muscled than in normal-muscled animals because of the reduced organ size of double-muscled animals (Fiems, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency for increased CI due to a higher BWb/BWpp ratio may be provoked by increased competition for space within the abdomen between the pregnant uterus and the digestive organs (Forbes, 1987). This competition may be more pronounced in doublemuscled than in normal-muscled cows, because of their reduced organ size and feed intake capacity on the one hand, and a higher calf BWb on the other (Fiems, 2012). The importance of BWb/BWpp ratio should not be exaggerated because only a low number of observations were in the classes with a low (n = 20) or a high ratio (n = 9), resulting in an increased CI.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the reduced reproductive performance are related to the double-muscling phenomenon (Fiems, 2012). A fetomaternal disproportion is typical for these animals, resulting in an increased frequency of dystocia (Eriksson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%